Impact of the Recent Changes in the Pharmacy Remuneration System in Portugal (2010-2014) - Moving from Paper to Reality - I Teixeira; JP Teixeira; S Costa (Formifarma, LDA., 2019)
Objective The pharmacies and wholesalers' remuneration system for the provision of medicines in Portugal went under structural changes with the Memorandum of Understanding in 2011, which intensified the degree of public pharmaceutical expenditure reduction requirements, in exchange for the financial international assistance. The objectives of the present study were: to provide an overview of the changes, its impact for pharmacies and recent advances towards a more comprehensive system. Methods Literature review and identification of changes; market analysis and distribution margins were computed using two nationwide databases with representative pharmaceutical dispensing data from ambulatory care; impact of changes and implications for the sector and pharmacies was accessed. Statistical analysis was performed using Statistical Analysis Software (SAS), Guide v4.1. Results The fixed linear remuneration system was replaced in 2012 by a regressive mark-up and minor fees system, per price range, determining the greatest modification to the distribution remuneration system during the last decades. An adjustment was made in 2014. The pharmaceutical market and the National Health System expenditure were reduced by 876 and 494 million euros, respectively, over the past four years. The loss of pharmacy and wholesaler remuneration was 322.8 million euros, higher than the established objective of 50 million euros. Conclusion Policy changes, reinforced with the Memorandum of Understanding, caused a large reduction in the remuneration of pharmacies, directly through cuts in margins and indirectly through decreases in prices. Several studies, published in the meantime, support the difficulties for the sector sustainability. Published in: Pharmacoeconomics. 2018: 3:117.